A spectroscopic study of the interaction of the VO2+ cation with the two components of chondroitin sulfate - Etcheverry, Susana Beatriz (1996)
The interaction of the vanadyl (IV) cation with N-acetyl-D-galactosamine, D-galactosamine, and D-glucuronic acid has been investigated by electron absorption spectroscopy at different mental to ligand ratios and pH values. In the case of D-glucuronic acid, a more detailed study was undertaken, using differential IR spectroscopy in solution. The results show that the cation interacts with the two nitrogenated molecules only at higher pH values, generating 2∶1 lig-and to metal complexes in which coordination occurs through two pairs of deprotonated OH groups of the rings. In the case of D-glucuronic acid, the IR-measurements allowed a wider insight into the structural characteristics of the complexes generated in acidic media. The involvement of the glycosidic oxygen atom in coordination, is suggested at pH=3.